FACTORS INFLUENCING PHYSICAL ACTIVITY OF STUDENTS OF EARLY COURSES OF HUMANITIES UNIVERSITIES - NABIEV Timur Erikovich («PHYSICAL CULTURE: UPBRINGING, EDUCATION, TRAINING», 2025)
The article is devoted to the study of the inﬂuence of physical exercise on the health of students in the educational environment. Physical activity is considered as a process of interaction between the subject and the external environment, allowing to optimize physical training through regular exercise without the use of specialized exercise machines and auxiliary devices. The eﬀectiveness of classes is determined by the possibility of improving the functional state of the body, reducing the level of morbidity and optimizing educational activities. The data of a sociological survey are presented, reﬂecting the attitude of students to regular physical exercise and identifying the factors that determine the motivation to lead an active lifestyle.